2018
DOI: 10.1039/c8cc07434h
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the sulfonylation of C–H bonds with the insertion of sulfur dioxide

Abstract: Recent advances in the sulfonylation of C–H bonds with the insertion of sulfur dioxide are summarized. C–H bond sulfonylation under transition metal catalysis or through a radical process has been developed. In some cases, the sulfonylation can be performed under catalyst- and additive-free conditions, or can be facilitated by visible light irradiation. The efficiency is also studied by merging the radical process and metal catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(30 citation statements)
references
References 169 publications
0
29
0
1
Order By: Relevance
“…When the photocatalyst was switched from PC-II to others, such as Ir-based photocatalysts [Ir(dF(CF 3 )ppy) 2 (dtbbpy)]PF 6 ( PC-I ) 21 and [Ir(dF(CF 3 )ppy) 2 (5,5′-dCF 3 bpy)]PF 6 ( PC-III ), 14 a ,22 4CzIPN , 23 Eosin Y , 24 and [Ru(bpy)3]Cl2 , 25 the yields decreased (entries 2–6). Substituting DABSO with other surrogates of sulfur dioxide (such as Na 2 S 2 O 5 and Rongalite), 26 or replacing the fluorine donor NFSI with Selectfluor led to a significantly lower conversion or no reaction (entries 7–9). Screening of the bases revealed that K 3 PO 4 was the optimal choice, while using other inorganic or organic bases resulted in diminished yields (entries 10 and 11).…”
Section: Resultsmentioning
confidence: 99%
“…When the photocatalyst was switched from PC-II to others, such as Ir-based photocatalysts [Ir(dF(CF 3 )ppy) 2 (dtbbpy)]PF 6 ( PC-I ) 21 and [Ir(dF(CF 3 )ppy) 2 (5,5′-dCF 3 bpy)]PF 6 ( PC-III ), 14 a ,22 4CzIPN , 23 Eosin Y , 24 and [Ru(bpy)3]Cl2 , 25 the yields decreased (entries 2–6). Substituting DABSO with other surrogates of sulfur dioxide (such as Na 2 S 2 O 5 and Rongalite), 26 or replacing the fluorine donor NFSI with Selectfluor led to a significantly lower conversion or no reaction (entries 7–9). Screening of the bases revealed that K 3 PO 4 was the optimal choice, while using other inorganic or organic bases resulted in diminished yields (entries 10 and 11).…”
Section: Resultsmentioning
confidence: 99%
“…[ 10 ] In contrast, combining C–H bond sulfonylation and direct incorporation of SO 2 in a three‐component approach still remains rare despite its advantage in terms of atom‐economy and convergence. [ 11 ]…”
Section: Methodsmentioning
confidence: 99%
“…[10] In contrast, combining C-H bond sulfonylation and direct incorporation of SO 2 in a three-component approach still remains rare despite its advantage in terms of atom-economy and convergence. [11] In the past decade, sustainable and environmentally-friendly visible-light photoredox catalysis has been successfully applied to C-H bond functionalization including a few examples of sulfonylation. [12] Indeed, Reiser et al developed a photocatalytic sulfonylation of heteroarenes including pyrrole, indole and thiophene using aryl sulfonyl chlorides as the sulfur-containing partner.…”
mentioning
confidence: 99%
“…Strategies for introduction of the same oxygenation state of SO 2 into two coupling partners have been intensively studied to improve the step economy and oxidative economy for sulfone synthesis. [19][20][21][22][23][24][25][26][27][28][29] Based on the observed effect of sulfur introduction from inorganic salts, [30][31][32][33][34][35][36] sulfur dioxide surrogates possessing diverse masking groups with disparate properties have been explored for the construction of sulfones. [37][38][39][40][41][42][43][44][45] Thiourea dioxide, an industrial raw material a base.…”
Section: Introductionmentioning
confidence: 99%